Cognition Mediates the Association Between Meaning in Life and Depression: Sex-Differentiated Analysis in Europeans Aged 50 and over - De Moraes-Ferrari, G (Springer, 2025)
This study aimed to explore whether immediate recall, delayed recall, and verbal fluency mediated the relationship between meaning in life and depression in a large sample of older adults from 17 European countries. The study also sought to investigate potential differences in mediation trajectories by sex. The data used were from the eighth wave of the SHARE project (year 2019), involving 24,277 individuals (13,874 women). The variables analyzed were: meaning in life extracted from the CASP-19 scale, tests for immediate recall, delayed recall and verbal fluency, and depression (12-item EURO-D scale). Depression was more prevalent among women. For both sexes, meaning in life was positively associated with immediate recall, delayed recall, and verbal fluency, while meaning in life was negatively associated with depression, indicating its potential to alleviate depressive feelings. The three cognitive domains significantly mediated the relationship between meaning in life and depression. Differences in indirect mediation effects between men and women were identified in the pathways: meaning in life → delayed recall → depression and meaning in life → verbal fluency → depression. The total indirect models for men and women differed significantly. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2025.
Keywords: Aging; Mental health; Cognition; Vulnerability; Meaning in life